Pengaruh PAD dan DBH Terhadapa Realisasi Belanja Daerah di Kabupaten Berau - Ratu, Ema Mustika; Effendi, Aji Sofyan; Awaluddin, Muhammad (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
ABSTRACT Ema Mustika Ratu. Effect of PAD and DBH on Regional Expenditures in Berau District. Supervisor by  Aji Sofyan Effendi and Muhammad Awaluddin.The purpose of this study was to determine the effect of Regional Original Revenue On Regional Expenditures especially in Berau district, cobaining relevant theory and empirical findings reflecting concepts rooted in Regional Original Revenue and Regional Expenditures.The data used in this study are secondary data with time series for the years 2010-2016 which include data on Regional Original Income, Revenue Sharing and Regional Expenditures in Berau District.The study was conducted using Multiple Linier Regression with the help of SPSS Version 20.The Result of hypothesis testing indicate that based on the correlation coefficient obtained can mean that the relationship of the variable  Original Regional Income (X1) and the variable profit sharing (X2) with the variable Regional Expenditures (Y). the relationship between Regional Original Income (X1) and Profit sharing (X2) with Regional Expenditure variable (Y) is strong, and the Profit Sharing Fund variable (X2) does not have a significant and self-effect on Regional Expenditure (Y).Keywords : Regional Original Income, Profit Sharing                    Funds, and Regional Expenditures